Saints of ninth- and tenth-century Greece - Kaldellēs, Antōnios Emm.; Polemēs, Iōannēs D. (Dumbarton Oaks medieval library, 2019)
Martyrdom of Nicholas the Younger -- Encomium of Nicholas the Younger / by the Presbyter Achaikos -- Funeral oration for Athanasios, Bishop of Methone / by Peter, Bishop of Argos -- Life of Peter, Bishop of Argos / by Theodore, Bishop of Nicaea -- Life and miracles of Theokletos, Bishop of Lakedaimon -- Life of Theodore of Kythera / by Leo -- Commemoration of Arsenios, Archbishop of Kerkyra.